Complete mitochondrial genome of Corydoras duplicareus (Teleostei, Siluriformes, Callichthyidae) - Qiaolin Liu; Baohong Xu; Tiaoyi Xiao (Mitochondrial DNA. Part B. Resources, 2019)
In this work, we reported the complete mitochondrial genome of Corydoras duplicareus. The total length of the mitochondrial genome is 16,667 bp, with the base composition of 32.90% A, 26.55% T, 25.94% C, and 14.61% G. It contains two ribosomal RNA genes, 13 protein-coding genes, 22 transfer RNA genes, and a major non-coding control region (D-loop region). The arrangement of these genes is the same as that found in the Siluriformes. All the protein initiation codons are ATG, except for cox1 that begins with GTG. The cytochrome c oxidase subunit I (COX1) amino acid sequence of C. duplicareus and other 27 species from 8 genera were used for phylogenetic analysis by maximum likelihood method. The topology demonstrated that all species are divided into two groups (Callichthyidae and Cyprinidae), and the C. duplicareus was clustered with C.nattereri.